2023
DOI: 10.3390/insects14030242
|View full text |Cite
|
Sign up to set email alerts
|

Floral Scents in Bee-Pollinated Buckwheat and Oilseed Rape under a Global Warming Scenario

Abstract: Many wild plants and crops are pollinated by insects, which often use floral scents to locate their host plants. The production and emission of floral scents are temperature-dependent; however, little is known about how global warming affects scent emissions and the attraction of pollinators. We used a combination of chemical analytical and electrophysiological approaches to quantify the influence of a global warming scenario (+5 °C in this century) on the floral scent emissions of two important crop species, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
0
0
0
Order By: Relevance
“…What is already well acknowledged is that olfactory signals are very important to bees to make flower choices because olfactory cues are easily learned and remembered by pollinators 90 and act in synergy with the reward and other floral features such as colour and the shape to attract specific pollinators 74 . Most studies showed that just a limited number of substances have a direct key function in attracting pollinators 61‐91 . Many substances appear almost universally present in the scent of flowers pollinated by honeybees, such as linalool and its analogues (found also in our studies), while others are characteristic of one or a few species.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…What is already well acknowledged is that olfactory signals are very important to bees to make flower choices because olfactory cues are easily learned and remembered by pollinators 90 and act in synergy with the reward and other floral features such as colour and the shape to attract specific pollinators 74 . Most studies showed that just a limited number of substances have a direct key function in attracting pollinators 61‐91 . Many substances appear almost universally present in the scent of flowers pollinated by honeybees, such as linalool and its analogues (found also in our studies), while others are characteristic of one or a few species.…”
Section: Discussionsupporting
confidence: 78%
“…Another aspect to consider is that nicotinaldehyde was found in plants not included in the fruit or bush trees, such as buckwheat nectar 66 and buckwheat honey, 67 in tobacco aroma, 68 and in linden honey 69 . In this last case it was not yet mentioned among the typical compounds of linden (otherwise called lime‐tree).…”
Section: Discussionmentioning
confidence: 99%